Managemen Produksi Dan Distribusi Tanaman Anggrek di DD Orchid Nursery - Didik Pudji Restanto; Mohammad Nur Khozin; Irvinia Rahmadyah; Alfina Damayanti; Wildan Ibnu Batuto; Djoko Soejono; Dwi Erwin Kusbianto (Postgraduate Program, University of Mataram, 2023)
Orchid plants are one of the ornamental plants that are widely known to the public in Indonesia and abroad. This type of plant was originally an epirite plant attached to other plants, but it produces very beautiful flowers. since the last decade, plant business activities have played a significant role in the center of economic growth. Batu City is a center for orchid production and marketing in East Java which is a priority for orchid plant development because orchid cultivation has added value when compared to ornamental plant businesses in general. The service method carried out is in the form of orchid cultivation training which includes: Making orchid plant packaging, orchid marketing strategy, customer segmentation, and evaluation method. Marketing agency involved in the distribution of official orchid plants that serve consumers such as hobbyists, collectors, and retailers around the Batu area. The quality of orchids can be seen from the stem of the orchid plant, the height of the orchid plant and the type of orchid plant. The selling price that occurs is basically through bargaining. determining the price of orchids in Batu is close to a free market where every farmer is free to determine the price as long as it does not deviate from the company. The payment system can be done in cash or transfer. Marketing of orchids involves several marketing institutions, namely retailers and collectors. Management of production and distribution of export quality orchids can be achieved with the support and methods that must be carried out such as good packaging of orchids, sophisticated marketing strategies, targeted customer segmentation and collaboration between institutions